The importance of functional taping in preventing wrist injuries in boxing: A medical view - de Sá, Kim Fonsêca Gomes; Luiz, Sthéfanie Xavier; Tabosa, Lily Anne Camara; Bomfim, Renata Oliveira Marques (Seven Editora, 2024)
Background: Functional bandages are a therapeutic tool widely used worldwide, not only for treatment, but also for injury prevention. Preventing extreme ranges of motion and reducing abnormal joint movement is the most obvious function of functional taping. The wrist is frequently injured in boxing, which often forces the athlete to abandon training and competitions. The study is necessary because there are few studies in Brazil that seek to compare the importance of functional taping as a measure to prevent wrist injuries in boxers. Objective: To analyze the importance of functional wrist taping, as a measure for preventing injuries in practitioners of this activity, as well as to relate the incidence of injury, the time of practice and the use or not of the bandage. Methodology: This was a cross-sectional study of an experimental nature, where 34 practitioners were evaluated, among them, 9 had wrist injuries and 25 did not have wrist injuries. Results: The study found that 77.8% of the practitioners had some injury and did not use the functional bandage, while 72% of the practitioners who did not have any type of injury used the bandage. Conclusion: In view of the results presented, the importance of the use of functional bandaging as an instrument to prevent wrist injuries was highlighted, as well as the need to deepen the application of the technique by medical professionals who work in sports medicine. DOI:https://doi.org/10.56238/sevened2024.026-054